PENGARUH INTEGRITAS DAN LOYALITAS PEGAWAI TERHADAP KEBIJAKAN PIMPINAN DAN DAMPAKNYA TERHADAP KINERJA DI LINGKUNGAN DINAS KOMUNIKASI DAN INFORMATIKA KOTA BATU - sujiyanto sujiyanto (MAGISTER MANAJEMEN UNISMA, 2020)
The purpose of this research are: to analyze the influence of integrity, employee loyalty to the leadership policy and its impact on the performance of existing employees in the environment of the Office of Communications and Information Batu City.The sample used in this reasearch is all employees who are in the environment Communications and Information Office Batu City which amounted to 77 people with the method of distributing questionnaires. The results of this study indicate that the integrity of employees of the Office of Communications and Information has a significant effect on improving employee performance, the loyalty of employees of the Office of Communications and Informatics have a significant effect on improving employee performance, the integrity of employees of the Office of Communications and Informatics have no significant effect on the policies of leaders, The loyalty of employees of the Office of Communications and Informatics have a significant effect on the leadership policy, as well as the leadership policy of the Office of Communications and Informatics has no significant effect on the improvement of employee performance. Keywords: integrity, loyalty, leadership policy and employee performance